Post Cataract Surgical Follow-Ups: Need to Revisit to Existing Guidelines - Acharya, Shivani; Patel, Minal; Singhal, Deepika; Tank, Amee; Thakkar, Yesha (National Journal of Community Medicine, 2017)
Background: Cataract surgery is one of the component of management of blindness, the overall management includes post-surgical regular follow-up and provision of additional aid. Objective of present study is to document post-surgery follow up and reasons for non-adherence. Methodology: Hospital based study, purposive sampling; 600(300 males and 300 females) who underwent cataract surgery in a tertiary care teaching hospital. Subjects were counselled for the standard guidelines and were followed to document the follow up compliance as per the standard protocols. Those who were lost to follow up were contacted by phone calls to understand the reasons for non-adherence. Results: Mean age 60 years+_9.1 years. The lost to follow up rate after second follow up was 16% and after third follow up was 82%; most common reason for non-adherence were: poor perceived needs (38%) followed by financial reasons (17.65%). Conclusion: In spite of appropriate pre-surgical counselling there was high lost to follow up due to poor perceived need, with advancement of the surgical techniques post-surgery follow-up needs to be revised for better adherence. Training of support staff for counselling can improve adherence.